Comparative Study of Predictive Models Based on Moving Averages Applied in Binary Options in the Financial Market - R. Hoff, Luccas; A. Berri, Rafael; N. Borges, Eduardo; Riker, André; Dalmazo, Bruno L. (Revista de Informática Teórica e Aplicada, 2024)
The technological market has been through significant advances in the last few years, and its application in different markets and business lines was driven by the COVID-19 pandemic. In this context, given the global economic crisis that was generated, some ways of earning money online were popularized, including the Binary Options market, which promises high gains but represents a volatile and risky financial niche. The aim is to evaluate the efficiency and assertiveness of these models applied in operations, in addition to analyzing the risks and possible returns. The aim is to provide a more in-depth understanding of the effectiveness of these models, considering the volatile and unpredictable characteristics of the Binary Options financial market. To achieve the proposed objective, different statistical models based on moving averages will be used to compare individual results and between possible combinations of the best classified. This study is expected to contribute to the understanding of the effectiveness of predictive models based on moving averages applied in Binary Options. The results obtained may offer valuable insights for investors and traders interested in this kind of negotiation, helping them to make informed decisions. Furthermore, this work is expected to stimulate the development of more accurate and efficient investment strategies, increasing the probability of success in financial markets. Finally, this study is expected to advance knowledge in the field of financial market forecasting, highlighting the importance of moving averages as a powerful predictive tool in Binary Options.